Cardiac remodelling in end stage heart failure: upregulation of matrix metalloproteinase (MMP) irrespective of the underlying disease, and evidence for a direct inhibitory effect of ACE inhibitors on MMP. Issue 5 (1st November 2002) - Reinhardt, D; Sigusch, H H; Henβe, J; Tyagi, S C; Körfer, R; Figulla, H R
Abstract : Objective: To investigate matrix metalloproteinases (MMP-2 and MMP-9) in heart failure caused by ischaemic and idiopathic dilated cardiomyopathy, and the impact of angiotensin converting enzyme (ACE) inhibition on MMP. Design and main outcome measures: MMP were extracted from myocardium of patients with heart failure (coronary artery disease, n = 13; idiopathic dilated cardiomyopathy (IDCM), n = 16) and from controls (n = 6). The active form of MMP-2 and MMP-9 was measured by enzyme linked immunosorbent assay; activity of MMPs by zymography; mRNA expression of MMPs by reverse transcriptase polymerase chain reaction. Results: Active MMP-9 was significantly increased in coronary artery disease (mean (SD) 1.6 (0.35) ng/ml) and IDCM (2.11 (0.54) ng/ml) in comparison with controls (0.53 (0.15) ng/ml). Increased MMP-2 was only found in IDCM (3.68 (0.41) ng/ml). There were corresponding increases in MMP activity but no upregulation of mRNA expression was found. The ACE inhibitors captopril and ramiprilate inhibited MMP-2 and MMP-9 activity in vitro (inhibitory capacity (IC50 ), in mmol/l: MMP-2: captopril 2.0 (0.16), ramiprilate 2.1 (0.3); MMP-9: captopril 1.65 (0.18), ramiprilate 2.0 (0.3)). Lisinopril inhibited MMP-9 significantly but did not inhibit MMP-2 in vitro (IC50 MMP-2: 7.4 (0.88); MMP-9: 7.86 (2.23)). Inhibition of MMP activity by ACE inhibitors was blunted by zinc excess. Conclusions: Upregulation of MMP-9 activity is common in the failing myocardium, independent of the underlying disease. Missing upregulation of transcription suggests that activation of latent forms of MMP is the source of increased MMP activity, rather than increased de novo synthesis. Some ACE inhibitors may influence MMP activity by a direct effect.